(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper introduces an ID card Management System that integrates 2-Dimensional Barcode which is responsible to produce more secure, reliable identification cards. This system will capture the personalized data including signature and photo of holder and dynamically generate an image of 2D Barcode containing the information provided and affix this barcode image on ID Card. This card can be used to validate and authenticate the holder. Main advantage of using 2D Barcode is its data encoding capacity, 2D Barcode is able to encode up to 500 bytes per square inch. Some data is used for error correction encoding provides the capability to tolerate the holes, cuts and dirt marks and makes 2D Barcode readable. There are varieties of 2D Barcodes available.This Paper uses one of the standard 2D Barcode PDF417 to demonstrate the ID card management. The paper discusses 2D barcodes and their encoding methodology, system workflow and architecture of proposed ID card management system.